Photodynamic Therapy for the Treatment of American Tegumentary Leishmaniasis: Evaluation of Therapies Association in Experimentally Infected Mice With Leishmania (Leishmania) amazonensis - do Nascimento Volpe, Roberta Ayres Ferreira (Laser Application in Medical Sciences Research Center, 2018)

(untitled) (J Lasers Med Sci)
Introduction: American tegumentary leishmaniasis (ATL) is a zoonotic disease caused by protozoan parasites of the genus Leishmania that affects the skin and mucous membrane. Currently, the available drugs for the treatment are injectable, with side effects, long-term treatment regimen and there is the possibility of drug resistance. Thus, alternative therapies have been tested, including photodynamic therapy (PDT). We evaluated the efficacy of PDT on its own and associated with the prescribed ATL treatment. Methods: BALB/c mice were infected with Leishmania (Leishmania) amazonensis and divided into 6 groups: Gluc+PDT, treated with Glucantime® and photodynamic therapy (PDT) with methylene blue (MB)/red LED (light-emitting diode); Gluc, treated with Glucantime®; PDT, treated with PDT with MB/red LED; Ampho+PDT, treated with amphotericin and PDT with MB/red LED; Ampho, treated with amphotericin; and control, which were infected but not treated. Two treatment cycles were performed. After 165 days of infection, the parasite load was determined. Results: Statistical differences were not found (P>0.05) between measures of volume and thickness of the infected footpads in the treated groups when compared with the control group. However, there was a significant reduction (P<0.05) in the parasitic load of the popliteal lymph nodes of the Gluc+PDT, Gluc, PDT and Ampho groups when compared to the control group. In the histological analysis of the infected footpads, the Gluc+PDT group presented a smaller amount of amastigote nests and lower intensity of the mononuclear infiltrate when compared to the Gluc and PDT groups. Conclusion: The results showed that although there is no significant difference in the evaluations of footpad size (thickness and volume), there is a downward measurement tendency in the Gluc+PDT group, as it can be observed by volume data and corroborated by parasite negative load.